Blockchain Technology for the Internet of Things and Future Cyber Security - Ahmed Mohammed; Rawaa Mohammed Abdul (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2024)
The purpose of this study is to make an attempt at doing a full survey of blockchain technology by describing its structure in addition to several consensus methods. They also investigate the difficulties and potential benefits associated with the Internet of Things and cyber security. In addition, they investigate potential future developments that the technology may accommodate in the next few years. The Internet of Things (IoT) aims to create a vast network of devices that generate and share data to enable intelligent interactions between people and their surroundings. The IoT is open, heterogeneous, and dynamic and might speed up real-time applications. These traits raise security, privacy, and trust issues. Thus, these issues limit IoT technology adoption. On the other side, Cybersecurity keeps unwanted people from getting into digital devices, networks, and data. This makes it less likely that data will be stolen or changed. It is about methods, processes, and routines that are carefully made to protect personal information and stop hacking. Cybersecurity has grown a lot because of cyberattacks. Cybersecurity tools include filters, encryption, secure passwords, and systems that look for threats and tell people what to do about them. Workers must learn how to do these things. The integration of blockchain technology with the Internet of Things (IoT) and cyber security serves to mitigate risks and enhance capabilities. This article presents a comprehensive analysis of blockchain security risk categories, drawing upon the intersection of Internet of Things (IoT) and cybersecurity challenges. Additionally, this study investigates the unique dangers and weaknesses associated with blockchain technology, as well as the security solutions designed to mitigate these risks. The use of blockchain technology in the domains of Internet of Things (IoT) and cyber security is advantageous owing to its attributes of openness, auditability, consistency, and security.